Social care for oncologic patient based on the medical outcomes study scale - Clediane Rita Portalupi da Trindade; Giselda Veronice Hahn (Universidade Federal de Santa Maria, 2016)
Aim: Measuring the social care for oncologic patients and checking whether results show gender differences. Method: Cross-sectional quantitative study design was employed. For data collection and analysis, the Medical Outcomes Study scale was used. Eighty male and female participants were interviewed. Data were statistically analyzed. Results: Men revealed that they have received more material and emotional care, access to information and positive social interaction. For women, only affective care was highlighted. The lack of a partner and the manifestation of a cancer in younger women have been factors reduced the level of social care. Conclusion: most participants have shown to hold social care, which allows us to infer that these individuals receive this basic care. We consider that it is important that health professionals are aware of the needs for care that women have mentioned, once the latter have shown the lowest availability of care